CUMS Imagined / Une vision de la SMUC - Gordon, Tom (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1999)
Encouraged by the engaging reflections of John Beckwith, the current President of the Canadian University Music Society, Tom Gordon, peers into the institutional crystal ball to imagine the challenges that lay ahead for the Society and the roles it might play in the future. Building on the organization's strengths of disciplined scholarship and the healthy diversity that characterizes our membership, a provocative role is envisaged for CUMS in communication around the many issues that unite the Canadian university music milieu.